8D.08: MATRIX METALLOPROTEINASE (MMP) 2 AND MMP9 ACTIVITY IS INCREASED IN CONDITIONS OF ALBUMINURIA ESCAPE UNDER CHRONIC RENIN-ANGIOTENSIN SYSTEM SUPPRESSION. (June 2015) - Pulido-Olmo, H.; Gracia-Prieto, C.F.; Somoza, B.; Aránguez, I.; Alvarez-Llamas, G.; Vivanco, F.; Barderas, M.G.; Kreutz, R.; Segura, J.; Fernández-Alfonso, M.S.; Ruilope, L.M.; Ruiz-Hurtado, G.
Abstract : Objective: Matrix metalloproteinase (MMP) 2 and MMP9 are involved in the pathophysiology of cardiovascular and renal diseases. The aim of this study was to analyze if albuminuria escape that some well-controlled hypertensive patients develop even under chronic renin-angiotensin system (RAS) suppression could be related to an increase in MMPs activity. Design and method: Concentration of MMP2/9 was analyzed by ELISA, and its activity by gelatin zymography in plasma samples from normoalbuminuric (n = 17) and albuminuric patients (moderate n = 14 or severe n = 8 albuminuria). The interaction between MMPs and its tissue inhibitor (TIMP) was analyzed by a novel assay developed in our laboratory using AlphaLISATM technology. The study of MMPs activity in the kidney as one of the target organs of this pathology was performed in Munich Wistar Frömter (MWF) rats, an experimental model of spontaneous albuminuria. Due to albuminuria is associated with a locus placed on chromosome 8, consomic MWF-8SHR rats, in which chromosome 8 from MWF rats was replaced by the respective one from spontaneously hypertensive rats (SHR), were also studied in order to analyzed whether MMP pattern is differentially associated with albuminuria development or conversely depends on a hypertensive. Results: Plasma MMPs concentrations were no different while their activities were increased in albuminuric patients as well as collagen type IV, one of their targets molecules. This increase in their activity is due to a significant decrease in MMP2/TIMP2 and MMP9/TIMP1 interaction in albuminuric patients. MMP2/9 activity was also increased in albuminuric MWF rats, and a positive correlation in MMP9 activity between plasma and kidney samples was observed. Consomic MWF-8SHR rats, showed a decrease in systemic and renal MMP9 activity compared with albuminuric MWF rats. Conclusions: i) The exclusive determination of circulatory MMP concentration could be underestimating its real activity in the clinical practice; ii) MMPs are multiorganic targets specifically involved in albuminuria escape that present well-controlled hypertensive patients even under chronic RAS blockade.